The Flat Slab Structural System for Cottage Construction - Pavlikov, Andriy; Pinchuk, Nataliia; Fenko, Oleksiy; Kyrychenko, Volodymyr (International Journal of Engineering and Technology, 2018)
A perspective area of construction is the cottage buildings construction in suburban scenic areas. It is expedient to use prefabricated reinforced concrete structures, namely the industrial flat slab structural system, to reduce the cost and the construction time. The structure of the frame includes columns, rigidity elements and slabs of overlapping. Design schemes and testing equipment are developed and proposed for research bearing capacity of the main structural elements of the frame. The experimental investigation results of the reinforced concrete slabs from flat-slab constructive system of buildings are presented. In this case, the assessment of the main structural elements of the frame, the details of their construction are given. The flat slab frame constrictive system has already proved in practice the effectiveness of its application for the multistorey residential buildings construction. On the basis of the conducted research, constructive solutions for buildings of cottage type are proposed. Today, this frame has undergone many improvements, and therefore it can be offered for solving such problems. The proposed constructive decisions will facilitate the massive introduction of industrial frame structure in housing construction to solve the problem of providing affordable housing for the population.Â Â Â